2018
DOI: 10.1038/s41598-018-29686-y
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Retrieval Competition Predict the Benefit of Repeated Testing

Abstract: Repeated testing leads to improved long-term memory retention compared to repeated study, but the mechanism underlying this improvement remains controversial. In this work, we test the hypothesis that retrieval practice benefits subsequent recall by reducing competition from related memories. This hypothesis implies that the degree of reduction in competition between retrieval practice attempts should predict subsequent memory for practiced items. To test this prediction, we collected electroencephalography (E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…mPFC involvement suggests that active control mechanisms related to those that promote behavioral flexibility underlie retrieval-induced forgetting, consistent with this structure’s role in mnemonic control 24 27 , 39 , 40 , 48 50 . Critically, the relationship between forgetting and declining prefrontal activity over repeated retrievals highlights how forgetting adapts memory to foster retrieval efficiency 24 26 , 51 . Together, these functional and neural parallels are consistent with the hypothesized species-general adaptive forgetting mechanism, although this bears careful scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…mPFC involvement suggests that active control mechanisms related to those that promote behavioral flexibility underlie retrieval-induced forgetting, consistent with this structure’s role in mnemonic control 24 27 , 39 , 40 , 48 50 . Critically, the relationship between forgetting and declining prefrontal activity over repeated retrievals highlights how forgetting adapts memory to foster retrieval efficiency 24 26 , 51 . Together, these functional and neural parallels are consistent with the hypothesized species-general adaptive forgetting mechanism, although this bears careful scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Recall has been used to study the effect of cognitive strategies, such as chunking and the use of mnemonics for memorization of things (such as large numbers) [40]. One interesting study reported the benefits of subsequent recall in retrieval operations where memories are related or competing [41]. The proverb "practice makes a man perfect" relates to the fortification of memory, and an investigation shows how retrieval plays an important role in this memory strengthening [42].…”
Section: Related Workmentioning
confidence: 99%
“…The proverb "practice makes a man perfect" relates to the fortification of memory, and an investigation shows how retrieval plays an important role in this memory strengthening [42]. Technologies such as functional magnetic resonance imaging (fMRI), magnetic resonance imaging (MRI), positron emission tomography (PET), and electroencephalography (EEG) played an active role in validating many recall related hypotheses [41,[43][44][45].…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, retrieval-induced forgetting has been tied to the tendency for related memories to compete during retrieval practice, a phenomenon known as competition dependence (Anderson, 2003;see Murayama et al, 2014, for a meta-analysis). Not only do brain signals linked to competition predict retrieval-induced forgetting (Kuhl, Dudukovic, Kahn, & Wagner, 2007;Staudigl, Hanslmayr, & Bäuml, 2010), changes in competition levels between the retrieval practice attempts can be used to classify which newly acquired word pairs are recalled after a week-long delay (Rafidi, Hulbert, Brooks, & Norman, 2018).…”
Section: Retrieval As a Cause Of Forgettingmentioning
confidence: 99%